Teaching Games for Understanding Training Model to Enhance Pencak Silat Movement Activities in Extracurricular Programs - Manik, Imda Wilambas; Sary, Dewi Maya (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
This study aims to examine the effectiveness of the Teaching Games for Understanding (TGfU) training model in improving Pencak Silat movement activities among students participating in extracurricular programs at UPT SMP Negeri 45 Medan during the 2023/2024 academic year. The research employed a quantitative approach with a quasi-experimental design, utilizing a pretest–posttest format. The participants consisted of 12 students actively involved in Pencak Silat extracurricular activities. Data analysis using the t-test indicated a significant improvement between pretest and posttest results, demonstrating that the TGfU model effectively enhanced students’ physical engagement and technical performance in Pencak Silat. These findings confirm that implementing TGfU-based training creates a more interactive, enjoyable, and meaningful learning experience, which promotes better motor activity and overall physical education outcomes.